Polyaspectivity in the training of future special education teachers - Kalinina, Tatiana (My University, 2021)
The article considers the problem of student’s readiness to work with children with special educational needs, and their ability to arrange, implement and manage pedagogical activities. The article considers and analyzes the professional readiness of future correctional teachers and its components, namely, motivation component, personal and emotional component, behavior and communication component, professional and pedagogical component. The conducted experiment revealed the unfavorable nature of pedagogical communication in future correctional teachers and confirmed that most students have an average level of professional readiness. Also, it helped to reveal the relationship between the year of study and the level of pedagogical communication. This indicates the need to arrange a special psychological correctional and developmental impact which would occur gradually in stages. The article proves the effectiveness of the “Program for Developing Student’s Personal Readiness to Work with Children with Special Educational Needs
Kalinina T. Polyaspectivity in the training of future special education teachers / Kalinina T // Modernization of the pedagogical system of tertiary education in higher education institutions : collective monograph / edited by G. F. Ponomarova, A. A. Kharkivska, L. O. Petrychenko and other; Municipal Establishment «Kharkiv Humanitarian Pedagogical Academy» of Kharkiv Regional Council. – Kharkiv : Publishing house Education and Science s.r.o., 2021. – С. 171–193
Keywords: здобувачі освіти, діти з особливими освітніми потребами, корекційний педагог, професійна готовність, корекційна робота, мотиваційний компонент, особистісно-емоційний компонент, поведінково-комунікативний компонент, професійно-педагогічний компонент, емпатія; student’s readiness, children with special educational needs, correctional teacher, professional readiness, correctional work, motivation component, personal and emotional component, behavior and communication component, professional and pedagogical component, empathy